УЎК 595.754 ЖАНУБИЙ ОРОЛБЎЙИ ЧЎЛ ҲУДУДЛАРИ ЯРИМҚАТТИҚҚАНОТЛИ (HEMIPTERA-HETEROPTERA) ҲАШАРОТЛАР ФАУНАСИ - Медетов, М.Ж.; Мусаев, Д.М.; Абдуллаева, Ж.К.; Гулимбетов, Б.Д.; Юсупова, А.Ж. (SCIENCE and SOCIETY, 2021)
The article presents the species composition of Hemiptera (bugs) insects common in the region, according to the results of studies carried out in the northwestern Kyzyl Kum desert and the Southern Aral Desert during 2019-2020. In the bug fauna, 97 species have been identified belonging to 12 families of 65 genera of the handcuffs subfamily. On the taxonomic distribution of bug species, data are given for dominant and recessive families, as well as for the types of phytophages and zoophages.